“ONE HEALTH” AS A RESOURCE FOR COST REDUCTION AND IMPROVEMENT OF RESULTS IN THE POULTRY INDUSTRY - Karklis, Mara Franco Bueno; Lopes, Beatriz; Bueno, Beatriz dos Santos; Manhoso, Fábio Fernando Ribeiro; Gaion, Lucas Aparecido; Contes, Matheus Jean; Andreotti, Laine de Castro; Spears , Rodolfo Claudio; Bueno, Patricia Cincotto dos Santos; Carratore, Carlo Rossi Del (INTERFERENCE: A JOURNAL OF AUDIO CULTURE, 2025)
This study analyzes the intersection between modern poultry farming and the "One Health" approach, demonstrating how the integration of human, animal, and environmental health principles can lead to economic gains and strategic competitiveness for the sector. Poultry farming, crucial for global food security, faces challenges such as market volatility and the emergence of diseases, like avian influenza.Implementing the "One Health" approach proposes proactive management that includes biosecurity, animal welfare, and healthy working conditions. Preventing outbreaks and reducing antibiotic use strengthen consumer trust and minimize production losses and treatment costs. By adhering to the "Five Freedoms" of animal welfare, the industry not only improves the quality of its birds but also its overall efficiency.In the environmental field, proper waste management, such as water reuse and the valorization of manure as biofertilizer, mitigates pollution and creates new revenue streams. The adoption of renewable energy sources, such as photovoltaic panels, also contributes to sustainability and a reduction in operational costs.In conclusion, "One Health" transcends a mere matter of ethical responsibility, acting as a robust business strategy. By investing in the health of their flocks, their workers, and the ecosystem, the poultry sector protects its operational base and builds a reputation for safety and sustainability that adds value to the final products, ensuring the long-term viability of the industry.